2019
DOI: 10.1111/epi.16360
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐long‐term subcutaneous home monitoring of epilepsy—490 days of EEG from nine patients

Abstract: ObjectiveTo explore the feasibility of home monitoring of epilepsy patients with a novel subcutaneous electroencephalography (EEG) device, including clinical implications, safety, and compliance via the first real‐life test.MethodsWe implanted a beta‐version of the 24/7 EEG SubQ (UNEEG Medical A/S, Denmark) subcutaneously in nine participants with temporal lobe epilepsy. Data on seizures, adverse events, compliance in using the device, and use of antiepileptic drugs (AEDs) were collected. EEG was recorded for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 36 publications
3
113
0
1
Order By: Relevance
“…Those studies confirmed previous observations regarding a presence of stable 24-h but also longer rhythms in epileptic seizures and interictal epileptiform discharges (IEDs). These rhythms varied with respect to the location of the epileptic focus as well as among individual patients (65)(66)(67)(68)(69)(70). Recent studies in humans and in rat models showed stable recurrence of seizures with regard to the phase of the circadian and multidien rhythms pointing toward endogenous mechanisms of such periodicities in epileptic phenomena, coregulation, and interrelationship between seizures and IEDs (67,71).…”
Section: Circadian Rhythms In Epilepsymentioning
confidence: 99%
“…Those studies confirmed previous observations regarding a presence of stable 24-h but also longer rhythms in epileptic seizures and interictal epileptiform discharges (IEDs). These rhythms varied with respect to the location of the epileptic focus as well as among individual patients (65)(66)(67)(68)(69)(70). Recent studies in humans and in rat models showed stable recurrence of seizures with regard to the phase of the circadian and multidien rhythms pointing toward endogenous mechanisms of such periodicities in epileptic phenomena, coregulation, and interrelationship between seizures and IEDs (67,71).…”
Section: Circadian Rhythms In Epilepsymentioning
confidence: 99%
“…The SubQ was used to record EEG in healthy subjects 29 as well as to detect clinically relevant electrographic seizures in epilepsy patients, showing high reliability and tolerance. 32,33 The device comes with dedicated software for automatic seizure detection and EEG visualization. The device is CE-marked, and multiple clinical trials are ongoing.…”
Section: Eeg Systemsmentioning
confidence: 99%
“…Prospective tolerance and safety data specific to subscalp EEG come from a single trial. 33 No serious adverse device-related events occurred, and the patients generally found the device easy to use, although this was only collected anecdotally. Minor annoyances were reported, such as difficulty with simultaneously wearing glasses, occasional nightly disconnections, and the necessity of wearing clothes at night to fix the external device.…”
Section: Tolerance and Safetymentioning
confidence: 99%
“…Such continuous monitoring systems may be enhanced by novel technology to continuously record EEG using ultraminiaturized subscalp EEG systems. 31 Continuous monitoring addresses several potential needs for people with epilepsy, including creating an objective and automated seizure diary, with the potential to overcome concerns about patient-reported diary inaccuracy 32,33 and creating a seizure alarm for carers. Furthermore, continuous monitoring of EEG opens the possibility of seizure forecasting, 32 which may be immensely valuable.…”
Section: S9mentioning
confidence: 99%